Essays on Economic Development in Commodity-Dependent Economies - (:unkn) unknown (My University, 2019)
This thesis belongs to the literature on natural resource dependence and brings a new perspective by focusing on the sub-Saharan African region. This dependence introduces numerous challenges for policy makers both in terms of fiscal and monetary policy. The main research question explored in this thesis is the following : to which extent sub- Saharan African governments can rely on fiscal and monetary policies to mitigate the adverse impacts of commodity dependence and trigger positive spillover and achieve sustainable growth? The second chapter of the thesis unfolds short-term versus long-term mechanisms of the resource curse by using a two-step analysis: an error-correction model is performed after co-integrating the explana- tory variables. Main findings highlight the crucial role of institutions. On the long run, the negative impact of the dependence is confirmed independently of the institution quality. However, countries with weak institutions are more vulnerable to the curse because the re- source dependence not only negatively impacts long-term growth but also adversely impacts the recovery process. Finally, in a strong in- stitutional environment, results points to a potential positive impact of natural resources during recovery process. In the third chapter, a panel vector auto-regressive model compares macro-economic interactions in the pegged CFA monetary union versus a comparable sample. Considering their export structure dominated by raw commodities, results suggests that the CFA zone members do not suffer from a loss of competitiveness from belonging to the monetary union. However, foreign direct investments fail to generate the same spillover effect in the CFA zone compared to non-CFA countries. The forth chapter provides insights on the optimal management of fiscal resources, especially during a windfall period. Growth elasticities of different government choices regarding revenue allocation is performed. Results show that in a con- t
Keywords: African Research